Mengenang hidup orang lain : sejumlah obituari - Rosidi, Ajip, 1938- (Jakarta : Kepustakaan Populer Gramedia, 2010)
Obituary of prominent Indonesian figures; collected of articles.
Includes bibliographical references and index.
Keywords: Obituaries -- Indonesia